THE SURFACE-CHEMISTRY OF HGBA2CUO4+DELTA - AN INVESTIGATION BY HIGH-RESOLUTION ELECTRON-MICROSCOPY - Zhou, W; Asab, A; Gameson, I; Jefferson, D; Edwards, P (1995)
The surface chemistry of the high-Tc superconductor HgBa2CuO4+σ has been studied using high-resolution electron microscopy. The material was found to be sensitive to both acetone and ethanol, but was quite stable under the electron beam. When crushed in air, the initial surface of the crystals was found to be coated by disordered Ba and Cu oxides with a Ba : Cu ratio 2:1 as determined by energy dispersive X-ray microanalysis. Following annealing under the electron beam, these disordered coating layers of approximately 20 Å thickness recrystallized into Ba2CuO3 crystallites which intergrew with the bulk HgBa2CuO4+σ on a variety of surface planes. © 1995.